NEW EUROPEAN RECORDS AND FIRST EVIDENCE OF EPIDERMAL STRUCTURES OF SLOANEA L. FROM THE ITALIAN OLIGOCENE – REVISED TYPE AND ORIGINAL MATERIAL OF PRINCIPI 1916 (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Leaves of Sloanea elliptica (Andreánszky) Z. Kvaèek & Hably and S. peolai (Principi) Hably, Tamás & Cioppi  with preserved organic structures were found during the study of Principi’s collection from the Oligocene flora of Santa Giustina. Fossil leaves of Sloanea elliptica have so far been recorded exclusively from the Palaeogene Basin of the Inner Carpathian Region, i.e. from the Lower Oligocene strata of Hungary and Slovenia, whereas S. peolai has been described from a single locality, Chiavon in Italy. Organic structure of S. peolai hitherto has not been recorded. The mass occurrence of Sloanea elliptica in the fossil assemblage of Santa Giustina indicates that its area was much more extensive than it was presumed. It was a characteristic element mainly of Oligocene floras, and even predominated them. This is the first record of the co-occurrence of two Sloanea species described on the basis of leaf remains. During the study 6 types and more than 30 illustrated specimens published in Principi's monograph were revised and identified as S. elliptica.
Keywords: Northern Italy; Oligocene; Sloanea; Cuticle; Principi; Types; Systematic revision